Synthesis and anti-inflammatory activity of celecoxib like compounds. (October 2013) - Ovais, Syed; Yaseen, Shafiya; Bashir, Rafia; Rathore, Pooja; Samim, Mohammed; Singh, Surender; Nair, Vinod; Javed, Kalim
Abstract : Nine novel 4-[3-(4-Dimethylamino-phenyl)-5-aryl-4, 5-dihydro-pyrazol-1-yl]-benzenesulfonamides (2a-i ) were synthesized and evaluated for their anti-inflammatory and antiproliferative activities. These compounds (2a-i ) showed moderate to strong anti-inflammatory activity in carrageenan rat paw oedema test. Compounds2b, 2d and2g showing comparable anti-inflammatory activity to that of reference drug celecoxib were evaluated for their ulcerogenic and analgesic activities. The effect of2b, 2d and2g on the content of NO, TNF-α and PGE2 in exudates from rat paw stimulated by carrageenan was also evaluated. The compound2c showed considerable antitumor activities against all 60 human tumor cell lines with effective GI50 (MG-MID) value of 3.63 µM. It exhibited maximum activity against melanoma (LOX IMVI and SK-MEL-5) cancer cell lines with GI50 value less than 2 μM.